The Impact of Spatial Planning Policy Implementation on Food Security in Padang City - Hidayah Retno Saputri; Adil Mubarak (Darul Yasin Al Sys, 2026)
The continued decline of productive rice fields in Padang City has weakened local food production capacity and increased dependence on rice supplies from other regions, highlighting the importance of effective spatial planning policy in protecting agricultural land. This study aims to examine the implementation of Padang City Regional Regulation Number 3 of 2019 concerning Regional Spatial Planning and its impact on food security, particularly in controlling the conversion of productive agricultural land. A descriptive qualitative approach was employed, with data collected through interviews, observation, and documentation. Research informants were selected using purposive sampling and included relevant government agencies and farmers affected by land conversion. The findings indicate that the implementation of Regional Regulation Number 3 of 2019 has not been optimal. Compliance among officials remains largely formal and procedural, while substantive supervision of agricultural land conversion is still ineffective. Policy implementation is also constrained by several structural problems, including weak inter-agency coordination, limited legal protection for sustainable agricultural land, inadequate data on land-use changes, and increasing pressure from regional development. These conditions have contributed to the continued reduction of rice fields, declining local food production, and growing dependence on food supplies from other regions. This study concludes that spatial planning policy implementation in Padang City requires stronger oversight, improved cross-sectoral coordination, and sustainable protection of productive agricultural land. The study contributes to public policy and food security studies by emphasizing the strategic role of spatial governance in safeguarding local agricultural resources and strengthening regional food resilience.